Talent identification and development in sport. An introduction - Baker, J.; Cobley, S.; Schorer, J.; Wattie, N. (Routledge handbook of talent identification and development in sport, 2017)
One of the most obvious trends in high performance sport over the past few decades has been the increasing systematization of athlete development and talent identification. There is increasing pressure to identify the most "talented" athletes as early as possible so that they can be placed in "optimal environments." Having a comprehensive understanding of the talent identification and selection process, and its implications for positive and negative developmental outcomes, is critical.